On stability and quasi-stability of a vector lexicographic quadratic boolean programming problem - Emelichev, V.A.; Nikulin, V. (Rev. Anal. Numér. Théor. Approx., 2001)
We consider a vector Boolean programming problem with the linear-quadratic partial criteria. Formulas of radiuses of two types of stability, necessary and sucient conditions of stability are found.